Day-ahead Low-Carbon Economical Dispatch of Integrated Energy System With CSP and ORC Based on Improved Imperialist Competitive Algorithm. Issue 1 (July 2021) - Zhang, Nenghan; Jian, Xiyan; Ding, Yibo; Wang, Yufeng; Chen, Lei
Abstract: In this paper an improved imperialist competitive algorithm(ICA) is used for day-ahead low-carbon economic dispatch of the integrated energy system(IES) with CSP and ORC. In order to enhance the utilization efficiency of different types of energy in IES, this paper introduces a concentrating solar power(CSP) plant to act as a power unit and an organic Rankine cycle(ORC) plant to decouple thermoelectric coupling. Combined with the facilities like the gas turbines(GT), power to gas(P2G), photovoltaic power(PV), etc. in IES, a day-ahead low-carbon economical dispatch model of IES is proposed to minimize the system cost. In the paper, the system cost is optimized by using the improved ICA. The analysis of the results of the example verifies that the proposed model is reliable and effective.